A Mask that Eats into the Face: Images and the Right of Publicity - Tushnet, Rebecca (The Columbia Journal of Law & the Arts, 2015)
In their eagerness to reward celebrities for the power of their “images,” and to prevent other people from exploiting those images, courts have allowed the right of publicity to distort the First Amendment. The power of the visual image has allowed courts to create an inconsistent, overly expansive regime that would be easily understood as constitutionally unacceptable were the same rules applied to written words as are applied to drawings and video games. The intersection of a conceptually unbounded right with a category of objects that courts do not handle well has created deep inconsistencies and biases in the treatment of visual and audiovisual media, particularly comics and video games. These problems show up both in First Amendment defenses and in copyright preemption analysis. The possible arguments one might offer for treating images differently are insufficient to justify this disparity. The Article concludes that, absent the distortion produced by images, the right of publicity would properly be understood as sharply limited.